A comprehensive assessment of life cycle environmental impact and economic feasibility of different red raspberry (Rubus idaeus L) cultivation systems - Xyderou Malefaki, Angeliki; Valanides, Nicolas; Manganaris, George A.; DeVetter, Lisa; Papadaki, Sofia; Krokida, Magdalini; Vyrkou, Antonia; Angelis-Dimakis, Athanasios (My University, 2025)
Red raspberry is considered a knowledge- and capital-intensive crop that targets a niche market globally; its quality attributes and enhanced health-promoting properties are highly appreciated by the consumers. In the context of the exponential growth in demand for this specialty crop that suffers from limited shelf life, it is imperative to expand raspberry cultivation by employing sustainably-sourced production models. In the current study, we used Cyprus as a case study that is characterised by increased production costs and lack of year-round production despite the fact that the latter is feasible under different production systems and cultivation methods in different altitude-related meso‑climates. Towards that goal, the current study assessed the life cycle environmental impact and life cycle costs of two different cultivation methods - open-field production that took place from May to November 2022 and protected cultivation in high-tunnels, from August 2023 to April 2024, using in both cases the same cultivar (Kwanza®) and plant type. The results indicated that protected cultivation has better environmental performance (3.7 mPt - milli eco-points - per kg of raspberry produced compared to 7.4 mPt for open-field production). Noteworthy, production cost is excessive and substantially higher compared to other countries; open-field production has a life cycle cost of 22.5 €/kg, while protected cultivation achieved a lower life cycle cost, equal to 14.0 €/kg yet still high. From an output perspective, a key observation is the increased yield of raspberries in protected cultivation as well as the enhanced water use efficiency of the crop, due to a reduction of the water footprint by 76 %. It is also important to highlight the increased harvest efficiency of the crop under high tunnel, with 500 g per plant compared to 350 g on open field cultivation. Hence, it is safe to conclude that despite the increased start-up costs and knowledge-intensive practices, the productivity of the crop is increased during the off-season months, that can be sold for a premium. The results highlight the environmental and economic impact of the two cultivation methods and will be useful for producers and crop advisors seeking to expand the raspberry cultivation in climates that resembles south-eastern Europe and are characterised as vulnerable to adverse climate change scenarios.
Keywords: Sustainable production; Soft fruits; Protected cultivation; Container production; Primocane; Water use efficiency